Multiagent Consensus Subject to Communication and Privacy Constraints - Maity, Dipankar; Tsiotras, Panagiotis (IEEE transactions on control of network systems, 2022)
We consider a multiagent consensus problem in the presence of adversarial agents. The adversaries are able to listen to the interagent communications and try to estimate the state of the agents. The agents have a limited bit rate for communication and are required to quantize the transmitted signal in order to meet the bit rate constraint of the communication channel. We propose a consensus protocol that is protected against the adversaries, i.e., the expected mean-square error of the adversary state estimate is lower bounded. In order to deal with the bit rate constraint, we propose a dynamic quantization scheme that guarantees protected consensus .